Secondary Organic Aerosol Formation Regulates Cloud Condensation Nuclei in the Global Remote Troposphere - Mingxu Liu; Hitoshi Matsui (Geophysical Research Letters)
Abstract Formation of secondary organic aerosols (SOA) through the atmospheric oxidation of organic vapors has potential to enable particle growth to cloud condensation nuclei (CCN)‐relevant sizes. In this work, we constrain a global aerosol model by using aircraft measurements to reveal the global importance of SOA formation in CCN production. Our improved model, with explicit size‐resolved aerosol microphysics and parametrizations of semivolatile organic oxidation products, presents a state‐of‐the‐art performance in simulating both particle number concentrations and organic aerosol concentrations dominated (80–95%) by SOA in the remote atmosphere, which have been challenges in previous modeling studies. The SOA formation in concert with aerosol nucleation contributes to more than 50% of CCN concentrations in those pristine environments featuring low background aerosol concentrations. We estimate that the SOA‐derived CCN alters the magnitude of cloud radiative forcing by ∼0.1 W m−2. Our findings underscore the necessity for aerosol‐climate models to represent controls on CCN concentrations by SOA production.